The Impact of Partnership Agreements Between Notaries Andservice Bureau Companies as a Strategy for Acquiring Clients - Karlini, Karlini; Suprayitno, Suprayitno; Sembiring, Rosnidar; Harianto, Dedi (LOCUS MEDIA PUBLISHING, 2025)
This study examines the growing trend of notaries partnering with service bureau companies as a marketing strategy to expand client reach, a practice that raises significant legal and ethical concerns. Using a normative juridical method with a prescriptive approach, supported by statutory and conceptual analysis as well as library and field research, the study evaluates the validity of a partnership agreement between Notary X and PT Y, its impact on the notary’s professional obligations, and the notary’s legal responsibility for deeds produced through such intermediaries. The findings show that the partnership agreement is legally invalid because it violates Article 1320 of the Civil Code, Article 16(1) of the UUJN, and Article 4(4) of the Notary Code of Ethics. The collaboration results in ethical violations, abuse of authority, degradation of authentic deeds into private documents, and legal liability for the notary based on fault under Article 1365 of the Civil Code.